Visual light flicker stimulation: enhancing alertness in sleep-deprived rats - Wang, Kun; Chen, Kang; Wei, Zilin; Wang, Tianhui; Wei, Aili; Gao, Xiujie; Qin, Yingkai; Zhu, Yingwen; Ge, Yi; Cui, Bo; Zhu, Mengfu (Frontiers in Neuroscience, 2024)
In the evolving field of neurophysiological research, visual light flicker stimulation is emerging as a promising non-invasive intervention for cognitive enhancement, especially in sleep-deprived conditions. This study aims to delineate the effects of specific flicker frequencies, namely 40 Hz and 20-30 Hz random flicker, on alertness recovery in sleep-deprived rats, focusing on their potential to modulate central fatigue. Employing a multidisciplinary methodology, we combined behavioral assessments using the Y-maze, in vivo electrophysiological recordings, and molecular analyses including c-FOS immunohistochemistry and hormone level measurements. Our findings reveal that both 40 Hz and 20-30 Hz flicker significantly improve behavioral performance in the Y-maze test, suggesting an enhancement of alertness. Neurophysiological, these flicker stimulations were shown to activate neural circuits in key brain regions such as the thalamus and hippocampus. Moreover, flicker exposure normalized cortisol and serotonin levels, which are crucial for stress response and mood regulation. Notably, c-FOS expression in brain regions associated with alertness and cognitive functions was significantly increased, indicating heightened neural activity. These results underline the potential of light flicker stimulation not only as a therapeutic tool to counteract the effects of sleep deprivation but also to enhance cognitive functions. Such findings pave the way for future translational research aimed at exploring light-based therapies in human subjects, potentially impacting fields related to occupational health and cognitive ergonomics.